Anxiety and COVID-19: Coronavirus Anxiety Scale scores in medical and non-medical personnel in urban hospitals in Guadalajara. A cross-sectional survey study. Issue 3 (16th March 2022) - García-Reyna, Benjamín; Castillo-García, Gilberto Daniel; Barbosa-Camacho, Francisco José; Cervantes-Cardona, Guillermo Alonso; Cervantes-Pérez, Enrique; Esparza-Estrada, Isaac; Brancaccio-Pérez, Irma Valeria; Silva-González, Gabriela; Fuentes-Orozco, Clotilde; Pintor-Belmontes, Kevin Josue; Guzmán-Ramírez, Bertha Georgina; Navarro, Dinorah Rodríguez; et al.
Abstract: The world is facing the worst health crisis in modern history. In addition to general concerns about the effects of COVID-19 on health, hospital personnel are developing numerous mental health conditions. This cross-sectional survey study evaluated the prevalence and severity of anxiety caused by the COVID-19 pandemic using the Coronavirus Anxiety Scale (CAS) in 2136 hospital employees. For the employees who presented scores ranging from 1–20 ( n  = 1090, 51%), the CAS mean score was 4.22 ( SD  = 3.95). The mean score was higher in women than men. By work category, non-clinical hospital personnel presented the highest CAS scores.